The EDGI new take on EDGE: EUS-directed transgastric intervention (EDGI), other than ERCP, for Roux-en-Y gastric bypass anatomy: a multicenter study - Krafft, Matthew R. (Endosc Int Open, 2019)
Background and study aims  Indications for accessing the duodenum, and/or excluded stomach in Roux-en-Y gastric bypass (RYGB) patients extend beyond diagnosis and treatment of pancreaticobiliary maladies. Given the high technical and clinical success of EUS-directed transgastric ERCP (EDGE) in RYGB anatomy, we adopted this transgastric (anterograde) approach to evaluate and treat luminal and extraluminal pathology in and around the excluded gut in RYGB patients. EUS-directed transgastric intervention (“EDGI”), other than ERCP, is the terminology we have chosen to describe this heterogenous group of transgastric diagnostic and/or interventional endoscopic procedures (transgastric interventions) performed via a lumen-apposing mental stent (LAMS) in select patients with RYGB. Patients and methods  A multicenter (n = 4), retrospective study of RYGB patients with suspected luminal or extraluminal pathology, in or around the duodenum and/or excluded stomach, underwent EDGI using LAMS between December 2015 and January 2019. Results  A total of 14 patients (78.6 % women; mean age, 55.7 + 12.4 years) underwent EDGI via LAMS. Technical and clinical success rates of EDGI were 100 %. The most common transgastric interventions were diagnostic EUS of extraluminal pathology (n = 6, 42.7 %) and endoscopic biopsy of gastroduodenal luminal abnormalities (n = 5, 35.7 %). Two moderate-severity adverse events due to LAMS maldeployment occurred during EUS-JG creation (14.3 %), and each instance was successfully rescued with a bridging stent. Conclusions  A variety of gastroduodenal luminal and extraluminal disorders in RYGB patients can be effectively diagnosed and managed using EDGI via LAMS.